WordPress beyond the basics : adding e-Commerce - Plumley, George (InfiniteSkills, 2014)
"In this WordPress for E-Commerce training course, expert author George Plumley teaches you how to use this blogging platform to build an E-Commerce website. This course is designed for users that already have a solid understanding of WordPress."--Resource description page.